Pengaruh Salinitas dan Pupuk Hayati Mikoriza terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum L.) - Firda Ramadini; Abdul Hasyim Sodiq; Endang Sulistyorini; Putra Utama (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
This study aimed to determine the effect of different salinity levels and the application of mycorrhizal biofertilizer on the growth and yield of tomato plants. The research was conducted from January 13 to March 23, 2024, on Jl Sultan Ageng Tirtayasa, Tirtayasa District, Serang Regency, Banten Province. The research was structured in a Randomized Group Design (RAK) with two factors. The first factor is salinity, which has four experimental levels: S0 = control, S1 = salinity 3-4 ds/m, S2 = salinity 5-6 ds/m, and S3 = salinity 7-8 ds/m. The second factor is Mycorrhiza Biological Fertilizer, which has four experimental levels: M1 = Mycorrhiza 5 grams, M2 = Mycorrhiza 10 grams, M3 = Mycorrhiza 15 grams and M3 = Mycorrhiza 20 grams. There are 16 combinations, and they are repeated three times to get 48 experimental units. Each experiment had two plants until there were 96 plants. Data were checked using DSAASTAT. If the variance test findings are significantly or very significantly different, then the Duncan Multiple Range Test (DMRT) is used at the 5% level. The results showed that administering a salinity level with a salinity concentration of 4-5 ds/m showed a significant difference in the fruit diameter parameters. Meanwhile, the salinity level with a salinity concentration of 3-4 ds/m showed significant differences in root length parameters. Meanwhile, the control treatment showed very significant differences in root weight parameters. Applying mycorrhizal fertilizer at a dose of 15 grams showed significant differences in root length, root weight, plant wet weight, and plant dry weight. Mycorrhiza failed to infect the roots of tomato plants because nothing showed any of the structures of mycorrhiza, namely hyphae, vesicles, arbuscular, and spores on the roots of tomato plants.